65.4k views
0 votes
Somebody help me please

Somebody help me please-example-1
User Yonatanmn
by
6.0k points

1 Answer

9 votes

Answer:

see explanation

Explanation:

given

(2x + 5)(2x - 1) ← expand using FOIL

(a)

= 4x² - 2x + 10x - 5 ← collect like terms

= 4x² + 8x - 5

(b)

using the method of completing the square on

4x² + 8x - 5 ← factor out 4 from the 1st 2 terms

= 4(x² + 2x) - 5

to complete the square

add/ subtract ( half the coefficient of the x- term )² to x² + 2x

= 4(x² + 2(1)x + 1 - 1) - 5

= 4(x + 1)² - 4 - 5

= 4(x + 1)² - 9

User Nataraj
by
6.4k points